Differentiated selves can surely be good for the group, but let's get clear about why. (2016) - Talaifar, Sanaz; Swann, William B.
Abstract: We applaud the goal of reconciling the self and group literatures and agree that a differentiated self may sometimes improve group outcomes. Nevertheless, greater precision regarding the underlying mechanisms is needed. Specifically, differentiated selves improve outcomes by overriding selfishness when they allow for personal regulation (being personally recognized and valued) rather than social regulation (specialization of labor).